2003
DOI: 10.1046/j.1469-8137.2003.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient availability during the early stages of colonization of fresh forage by rumen micro‐organisms

Abstract: Summary• During grazing, it is unclear to what extent rumen conditions cause immediate physical damage to intact, ingested plant cells and whether this coincides with microbial degradation of plant constituents.• An in vitro model that included or excluded rumen microorganisms was used to investigate the extent of membrane damage and release of cell constituents from model and forage plants in relation to fermentation parameters.• Significant ion release after 2 h indicated that plant cell membranes were intol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
1
14
0
1
Order By: Relevance
“…Thus, in the present study, a DM loss of approximately 35 % from the incubated herbage is potentially independent of micro-organisms and is due to plant-based processes and activities associated with plant cell death. A similar discrimination of plant-and microbium-based activities pertaining to the release of plant vacuolar contents has previously been demonstrated (Kingston-Smith et al 2003b).…”
Section: Discussionsupporting
confidence: 73%
“…Thus, in the present study, a DM loss of approximately 35 % from the incubated herbage is potentially independent of micro-organisms and is due to plant-based processes and activities associated with plant cell death. A similar discrimination of plant-and microbium-based activities pertaining to the release of plant vacuolar contents has previously been demonstrated (Kingston-Smith et al 2003b).…”
Section: Discussionsupporting
confidence: 73%
“…However, it is clear that either relatively little of the available total carbohydrate from the plant substrate was released to the footprint for microbial uptake, or carbohydrate was only transiently present in the footprint, being immediately taken up by the planktonic bacteria. The latter seems likely from the linear (rather than exponential) increase in the carbohydrate signal originating from the bacterial pellet and previous results [33]. Also, as availability of soluble carbohydrate affects plant cell survival under anoxic and hypoxic conditions [4548] so reserves of cellular carbohydrate in plant cells could be quickly depleted on exposure to the rumen environment (anaerobic, 39 °C) due to demands from de novo synthesis of stress-related proteins.…”
Section: Discussionmentioning
confidence: 93%
“…For example, in fresh-forage-based systems not all of the soluble nutrients are immediately available as a result of mastication (Boudon and Peyraud, 2001;Kim et al, 2006) or as a result of exposure of ingested viable plant cells to the rumen environment (Kingston-Smith et al, 2003b). Although it has been clearly demonstrated that dietary protein can be directly utilised or broken down in the rumen by microbial taxa (Wallace et al, 1997), in situ the plant protein may be protected from degradation by complexing with phenolic compounds (Theodorou et al, 2000;Winters and Minchin, 2001) or can be inaccessible due to being compartmented within plant cells (Kingston-Smith and Theodorou, 2000).…”
Section: Impact Of Diet On Rumen Microbial Biomassmentioning
confidence: 99%